Thermal and Dielectric Behavior Studies of Poly(Arylene Ether Sulfone)s with Sulfonated and Phosphonated Pendants. (24th August 2016) - Ganesh, Shimoga D.; Pai, Vasantakumar K.; Kariduraganavar, Mahadevappa Y.; Jayanna, Madhu B.
Abstract : The present paper discusses the aspects of the synthesizing valeric acid based poly(ether sulfone)s with active carboxylic acid pendants (VALPSU) from solution polymerization technique via nucleophilic displacement polycondensation reaction among 4, 4′-dichlorodiphenyl sulfone (DCDPS) and 4, 4′-bis(4-hydroxyphenyl) valeric acid (BHPA). The conditions necessary to synthesize and purify the polymer were investigated in some detail. The synthesized poly(ether sulfone)s comprise sulfone and ether linkages in addition to reactive carboxylic acid functionality; these active carboxylic acid functional groups were exploited to hold the phenyl sulphonic acid and phenyl phosphonic acid pendants. The phenyl sulphonic acid pendants in VALPSU were easily constructed by altering active carboxylic acid moieties by sulfanilic acid using N, N′-dicyclohexylcarbodiimide (DCC) mediated mild synthetic route, whereas the latter one was built in two steps. Initially, polyphosphoric acid condensation with VALPSU by 4-bromoaniline and next straightforward palladium catalyzed synthetic route, in both of which acidic pendants are clenched by polymer backbone via amide linkage. Without impairing the primary polymeric backbone modified polymers were prepared by varying the stoichiometric ratios of respective combinations. All the polymers were physicochemically characterized and pressed into tablets; electrical contacts were established to study the dielectric properties. Finally, the influence of the acidic pendants on the dielectric properties was examined.